Crystalline nephropathy due to adenine phosphoribosyl transferase deficiency as a cause of renal allograft dysfunction - Umapati Hegde; Rajapurkar Mohan; Gang Sishir; Amit Jojera; Shailesh Soni (Archives of Clinical Nephrology - Peertechz Publications, 2021)
APRT deficiency is a rare but under recognized genetic disease.  Recurrent urolithiasis and DHA nephropathy are the two clinical manifestations of APRT deficiency and diagnosis can be made at any age and recurs after renal transplant. Allopurinol is the cornerstone in preventing recurrence.  APRT activity assay and genetic testing are useful for confirmation of diagnosis, for family screening and in difficult cases of urolithias or crystalline nephropathy.